Mg/Al HYDROTALCITE-LIKE SYNTHESIZED FROM BRINE WATER FOR EOSIN YELLOW REMOVAL - Eddy Heraldy; Triyono Triyono; Karna Wijaya; Sri Juari Santosa (Universitas Gadjah Mada, 2011)
Attempts to synthesis of Mg/Al HTlc using magnesium from several raw material resources are widely investigated. One of raw material would purpose as source of magnesium to synthesis of Mg/Al HTlc is brine water which is well known as the desalination process wastewater. Mg/Al HTlc are widely investigated for their potential applications in research and industrial processes as adsorbents, anionic exchange, catalysts and /or catalyst precursors for the preparation of inorganic materials and pharmaceutical industry excipients. As adsorbents, Mg/Al HTlc are receiving greater interests in the environmental community due to their high adsorption capacity. However, there is no literature available on the synthesis of Mg/Al HTlc from brine water except from artificial seawater. The objective of this research is to synthesis of Mg/Al HTlc from brine water and its ability tested for eosin yellow (EY) removal. Characterization of the Mg/Al HTlc synthesized was confirmed through X-ray Diffraction and FT-IR Spectroscopy. The effect of various experimental parameters was investigated using a batch adsorption technique. In this manner, the adsorption isotherms, adsorption kinetics, and pH effects upon EY adsorption on Mg/Al HTlc were examined. The result showed that EY data fit well with the pseudo-second order kinetic model. The isothermal data could be well described by the Freundlich equation. The adsorption capacity was 2.41 × 10-1 mol g-1, and adsorption energy of EY was 24.89 kJ mol-1.